M|G|∞ queue busy cycle renewal function for some particular service time distributions - Ferreira, M. A. M. (Proceedings of the International Conference: Quantitative Methods in Economics (Multiple Criteria Decision Making XII), 2004)
In this paper we present formulas to compute the busy cycle renewal function for the M vertical bar G vertical bar infinity. queue, considering service time distributions that arise when we study parameters related to the busy period. The busy cycle renewal function in t gives the mean number of busy periods that begin in [0, t].